CHEMICAL ENGINEERING RESEARCH II TECHNO-ECONOMY ANALYSIS OF MERCURY REMOVAL FROM CRUDE OIL WITH INTERNAL STRIPPING GAS - Denabil Hendraputra, Farrel
Mercury has been identified as a dangerous substance in the chemical industry. The loss caused by mercury could reach billions of dollars annually. Mercury contained in crude oil and natural gas flow could lead to corrosion and process equipment contamination. One of the methods that was developed to separate mercury from the crude oil and natural gas flow is by using its own internal stripping gas. However, this mercury separation method was relatively new, so a further research needs to be done to the process. The purpose of this study was to study the technology and economy aspect of mercury separation using its own internal stripping gas. This research was conducted to determine the proper thermodynamics property package for mercury separation process modelling and to evaluate its economic feasibility. The feed that was used in this study is an imitation that refers to the characteristic of Tangguh condensate from Indonesia. The mercury concentration in the feed flow was 500 ppbwt and the maximum mercury concentration in the product was 16 ppbwt. This study was conducted by simulation using Aspen HYSYS V10 and Microsoft Excel software. The study shows the proper thermodynamics property package for mercury separation process modelling is Peng-Robinson (PR) with the binary interaction parameter estimated from mercury solubility in alkanes data. For pentane to decane homologue, the binary interaction parameter (Y) is found to be depended on molecular weight (X) with correlation as follows Y = 0,6464 - 0,153ln(X). This correlation is extrapolated to predict the binary interaction parameter in Tangguh condensate’s component. The capital cost needed to build the process with production rate of 765 barrels crude oil per day is USD 1.30 million. The operating cost needed to build the process is USD 21.50 million annually (without depreciation) or equivalent to USD 3,01 per barrel crude oil to process the crude oil to fit the mercury concentration specification of 15 ppbwt in the product.